Imaging Predictors of Neurologic Outcome after Pediatric Arterial Ischemic Stroke - Jiang, Bin (Stroke, 2020)
BACKGROUND AND PURPOSE: To assess whether initial imaging characteristics independently predict one-year neurological outcomes in childhood arterial ischemic stroke (AIS) patients. METHODS: We used prospectively collected demographic and clinical data, imaging data, and one-year outcomes from the Vascular effects of Infection in Pediatric Stroke (VIPS) study. In 288 patients with first-time stroke, we measured infarct volume and location on the acute magnetic resonance imaging (MRI) studies, and hemorrhagic transformation on brain imaging studies during the acute presentation. Neurological outcome was assessed with the Pediatric Stroke Outcome Measure (PSOM). We used univariate and multivariable ordinal logistic regression models to test the association between imaging characteristics and outcome. RESULTS: Univariate analysis demonstrated that infarcts involving uncinate fasciculus, angular gyrus, insular cortex, or that extended from cortex to the subcortical nuclei were significantly associated with poorer outcomes with odds ratios ranging from 1.95 to 3.95. All locations except the insular cortex remained significant predictors of poor outcome on multivariable analysis. When infarct volume was added to the model, the locations did not remain significant. Larger infarct volumes and younger age at stroke onset were significantly associated with poorer outcome, but the strength of the relationships was weak. Hemorrhagic transformation did not predict outcome. CONCLUSION: In the largest pediatric AIS cohort collected to date, we showed that larger infarct volume and younger age at stroke were associated with poorer outcomes. We made the novel observation that the strength of these associations was modest and limits the ability to use these characteristics to predict outcome in children. Infarcts affecting specific locations were significantly associated with poorer outcomes in univariate and multivariable analyses, but lost significance when adjusted for infarct volume. Our findings suggest that infarcts which disrupt critical networks have a disproportionate impact upon outcome after childhood AIS. NON-STANDARD ABBREVIATIONS AND ACRONYMS: Acute Ischemic Stroke (AIS); Vascular effects of Infection in Pediatric Stroke (VIPS); Pediatric Stroke Outcome Measure (PSOM); Percentage Infarct Volume (PIV)